Zoneamento geoambiental analítico da bacia do Rio Clarinho a partir da técnica de avaliação de terreno, na escala 1:50.000 - Guerrero, João Vitor Roque (2014)
Nowadays, the disorderly way in what happens the human occupation on the physical environment, generates serious environmental, social and economic problems. In order to assuage these problems, many works in the geosciences area concerns with this subject, trying to mitigate these processes, mainly from the territorial planning. The most commonly tool used for territorial planning is the geo-environmental zoning, consisting of, from a prior knowledge of the local physical environment, defining areas of interest, where it may propose limitations and potential for its use and occupation. In this context, this work aimed to generate a chart of analytical geo-environmental zoning of the Rio Clarinho watershed (Brazil) on the scale of 1:50.000. The basin is located in the northeast of the state of São Paulo and presents area of 40.87 km ². The proposed zoning had as a major factor the relief forms of the area, from the technique known as the Land Evaluation. This technique analyzes the forms of relief (landforms), since they are reflections of the natural processes acting on the materials of the earth's surface and, therefore, should reflect the conditions thereof, providing conditions that are proposed and the potential restrictions on use and occupation of the área. As a result, the geoenvironmental zoning of Rio Clarinho chart was generated and pointed to five geoenvironmental units, where proposals for potential and limitations of land use according to the characteristics of the physical environment were presented.